Bio‐Inspired Soft‐Rigid Hybrid Smart Artificial Muscle Based on Liquid Crystal Elastomer and Helical Metal Wire. Issue 17 (18th January 2023) - Zhao, Limeng; Tian, Hongmiao; Liu, Haoran; Zhang, Weitian; Zhao, Fabo; Song, Xiaowen; Shao, Jinyou
Abstract: Artificial muscles are of significant value in robotic applications. Rigid artificial muscles possess a strong load‐bearing capacity, while their deformation is small; soft artificial muscles can be shifted to a large degree; however, their load‐bearing capacity is weak. Furthermore, artificial muscles are generally controlled in an open loop due to a lack of deformation‐related feedback. Human arms include muscles, bones, and nerves, which ingeniously coordinate the actuation, load‐bearing, and sensory systems. Inspired by this, a soft‐rigid hybrid smart artificial muscle (SRH‐SAM) based on liquid crystal elastomer (LCE) and helical metal wire is proposed. The thermotropic responsiveness of the LCE is adopted for large reversible deformation, and the helical metal wire is used to fulfill high bearing capacity and electric heating function requirements. During actuation, the helical metal wire's resistance changes with the LCE's electrothermal deformation, thereby achieving deformation‐sensing characteristics. Based on the proposed SRH‐SAM, a reconfigurable blazed grating plane and the effective switch between attachment and detachment in bionic dry adhesion are accomplished. The SRH‐SAM opens a new avenue for designing smart artificial muscles and can promote the development of artificial muscle‐based devices. Abstract : Inspired by human arms, a soft‐rigid hybrid smart artificial muscle (SRH‐SAM) is proposed. The performance of the SRH‐SAMs as regards the shape morphing, load‐bearing capacity, and sensing functions is difficult to be achieved by traditional artificial muscles. This opens a new avenue for designing smart artificial muscles and can promote the development of artificial muscle‐based devices.